LEADERSHIP DAN MANAGERIALSHIP - Hasanah, Siti Nur Hidayatul; Patoni, Achmad; Maunah, Binti (Jurnal Manajemen Pendidikan Islam Darussalam, 2024)
This research aims to find out about leadership, managerial ship, and the similarities and differences between leadership and managerial ship. Even thought the two terms are closely related and are often used interchangeably, they have differences. A leader has the task of giving direction and giving subordinates the task of moving towards the same goal and manager function in the field of management implementation. The method used in this research is library research, data was obtained from various sources such as books, articles,s and journals about leadership and management. The results of the research are: 1) leadership is the art and ability that a person has in using his power to influence other people to carry out certain activities to achieve predetermined goals, 2) managerial ship is managerial ability in preparing implementation plans as well as placing employees in accordance respective position, 3) the similarity between leadership and managerial ship is that both have responsibility and subordinates, 4) the differences is that in leadership, a leader is tasked with directing and moving subordinates, whereas in managerial ship, a manager has duties according to management functions.